2016
DOI: 10.18805/ijar.11176
|View full text |Cite
|
Sign up to set email alerts
|

Receiver operating characteristic analysis of milk lactosefor identification of mastitis in buffaloes

Abstract: Receiver operating characteristic (ROC) analysis is a simple statistical tool used to classify a diagnostic indicator in terms of area under a ROC curve (AUC) and to develop potential threshold values of a diagnostic indicator. Milk lactose was analyzed by ROC analysis to see its accuracy to discriminate infected and healthy udder quarters, and to develope an optimum threshold value along with corresponding sensitivity (Se), specificity (Sp) and positive likelihood ratio (LR+) value. Data for the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, Patbandha et al (2016) indicated that milk lactose decreased with increase in severity of infection. Milk (Faroult et al, 2003).…”
Section: Resultsmentioning
confidence: 98%
“…However, Patbandha et al (2016) indicated that milk lactose decreased with increase in severity of infection. Milk (Faroult et al, 2003).…”
Section: Resultsmentioning
confidence: 98%
“…Physicochemical parameters (freezing point, conductivity, fat content, protein content, lactose content, mineral content and vitamins) were measured by a "Lactoscan" (Milkotronic LTD Europe) according to the manufacturer's instructions (Patbandha et al 2016) Samples preparation and dilutions for microbiological analysis were performed according to the recommendations of the International Dairy Federation (IDF, 1991).…”
Section: Methodsmentioning
confidence: 99%